Variations of isozyme and morphological characters of malaria vector and non-vector Anopheles subpictus Grassi - RUBEN DHARMAWAN; DARUKUTNI DARUKUTNI; SATIMIN HADIWIDJAJA; ADI PRAYITNO (Biodiversitas Journal of Biological Diversity, 2005)
The aim of the study was to show genetic variations of malaria vector Anopheles subpictus in East Flores, East Nusa Tenggara Province and non-vector in Banjarnegara, Central Java Province by isozyme electrophoresis and refined morphological examinations as isozymes and morphological characters are known as gene influenced factors. An. subpictus females were collected by using animal and human bait collection and reared individually in the laboratory. Progenies were used as materials for electrophoretic examination after eggs and larvae were morphologically confirmed as the species investigated. Each progeny was run on horizontal starch electrophoresis in a separate well according to Green et al. (1990), Sukowati et al. (1999) and Dharmawan et al. (2002) with modification. The visualized isozymes were malate dehydrogenase (Mdh), lactate dehydrogenase (Ldh), alkaline phosphatase (Alp), alpha esterase (Î±Est), beta esterase (Î²Est), malic enzyme (Me), leucine aminopeptidase (Lap), and acid phosphatase (Acp). Zymograms showed that Mdh, Ldh, Alp, Î±Est and Me had been varied between vector and non-vector species. Refined morphological examination on larvae showed different number of branches of their inner clypeal hairs and observation on eggs revealed different size and ridge numbers. We concluded that An. subpictus in East Flores was genetically and morphologically different from Banjarnegara and suggested that the two variants might be members of An. subpictus species complex. Key words: isozyme, morphology, Anopheles subpictus complex, Banjarnegara, East Flores.